Public Perception of Paragliding Sport at Haruman Jingga Hill - Rizan Julian; Tedi Supriyadi; Rizal Ahmad Fauzi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the public perception of paragliding sports at  Haruman Jingga hill. Using a phenomenological approach, data were collected through observation and in-depth interviews with local people, paragliding athletes, tourists, and traders. Thematic analysis using NVivo 12 Pro software produced the main themes regarding public perception of paragliding sports. The results of the study showed that the public has diverse insights into paragliding sports, public interest in paragliding sports and the level of security that is already known to the public is quite good because the facilities are adequate. The public generally views paragliding sports positively and the economic impact that provides jobs and business opportunities for the community and socially, this sport encourages interaction with tourists and other communities, although there are concerns about the potential for places to be misused by people with bad intentions. then the importance of sustainable management in order to further minimize the negative impacts caused.